Values Pedagogy and Student Achievement Contemporary Research Evidence - Lovat, Terence; Dally, Kerry; Clement, Neville; Toomey, Ron.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Under the weight of a combination of forces, many of the older paradigms of learning are being questioned in our time. Among the updated research that elicits such critique is that which deals directly with effective pedagogy, clearly illustrating the enhanced effects on learning when it is dealt with as a holistic developmental enterprise rather than one concerned solely with content, technique and measurable outcomes. This research includes volumes of empirical evidence and conceptual analysis from across the globe that point to the inextricability of values as lying at the heart of those forms of good practice pedagogy that support and facilitate the species of student achievement that truly does transform the life chances of students. This research indicates that the combination of values rich learning environments and values discourse (that is, the holism of implicit and explicit pedagogy) has potential for positive influence on learning outcomes, most markedly for those deemed likely to fail without such pedagogical intervention. Values Pedagogy and Student Achievement - Contemporary Research Evidence uncovers, explores and appraises those volumes of evidence and analysis, illustrating their pertinence to student achievement, the vexed issue that lies at the heart of all for which education stands.
About the Authors -- Preface -- 1: Values and Good Practice Pedagogy -- 2: History and Philosophy of Values and Virtues -- 3: Values and the Sciences -- 4: Values and Wellbeing -- 5: Values and the Curriculum -- 6: Values and Personal Integrity -- 7: Values and Social Engagement -- 8: Values and Behaviour -- 9: Values Pedagogy and Academic Diligence -- 10: Values Pedagogy and Teacher Education -- 11: The Ambience and Discourse of Values Pedagogy -- Index.
Keywords: Education; Education -- Philosophy; Education; Educational Philosophy; Learning & Instruction; Teaching and Teacher Education; Educational Policy and Politics